If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + 6x + -2x = 14 Combine like terms: 6x + -2x = 4x -6 + 4x = 14 Solving -6 + 4x = 14 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 4x = 14 + 6 Combine like terms: -6 + 6 = 0 0 + 4x = 14 + 6 4x = 14 + 6 Combine like terms: 14 + 6 = 20 4x = 20 Divide each side by '4'. x = 5 Simplifying x = 5
| (7r+5)(2r-6)=0 | | (4-5i)/(5-1) | | 2z+13=8z+1 | | 2x-1+x=-28 | | 9y+8=6y+1 | | X+4-3=6*5 | | 2-x+6x=37 | | 42=(960)(177/360)r | | 4x+5ys=12 | | y+(-2)=100 | | 15+x=2x+6 | | -13=2x+5x+8 | | 71+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | 5(p+2)+6(-3-p)=0 | | 7x^2-11x+5=0 | | 4x^2-80x+144=0 | | 4+6x+2x=76 | | 1+[-5+(-2x+3)]=25-[-(3x+4)-(4x+3)] | | y=7x+-10+-3 | | 5p^2-125=0 | | -3x+7-4x=-77 | | x+x+2+x+4=66-x | | 315=30z | | -8x^2+4x+5=0 | | 0=4x^2-81 | | 4x^6+x^3-6x^2-x^3-5x^2+3x= | | y=13+7x | | 2k-5=4k+3 | | x-10-x=8 | | -5×(1/3)^n-1 | | X-2y+2z=-1 | | r-6=7 |